2018
DOI: 10.31487/j.pdr.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Differences in measurements of hyperactivity between objective testing using infrared motion analysis (QbTest) and behavioural rating scales when comparing problems in alerting functions and response inhibition during the clinical assessment of ADHD

Abstract: Introduction: Little is known how problems in alerting functions or response inhibition affect objective infrared activity measurements during a continuous performance test (QbTest) despite an increasing use of these tests for the clinical assessment of ADHD. Difficulties in alerting functions and response inhibition are both associated with the presence of behavioural features in all three core domains of ADHD, i.e. inattention, impulsivity and hyperactivity. We hypothesized that objective infrared activity m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In a large epidemiological study, Epstein et al (2006) found that unexpectedly, omission errors were associated with hyperactivity symptoms (and not with inattention symptoms), whereas commission errors were related to impulsivity symptoms, hyperactivity, and inattention symptoms. Likewise, a recent study demonstrated that the levels of hyperactivity or impulsivity during CPT performance might be associated with basic attentional rather than inhibition processes (Vogt et al, 2018). It has been suggested that excessive motoric activity, such as fidgeting during a cognitive performance, reflects efforts to modulate attention and alertness (Hartanto et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In a large epidemiological study, Epstein et al (2006) found that unexpectedly, omission errors were associated with hyperactivity symptoms (and not with inattention symptoms), whereas commission errors were related to impulsivity symptoms, hyperactivity, and inattention symptoms. Likewise, a recent study demonstrated that the levels of hyperactivity or impulsivity during CPT performance might be associated with basic attentional rather than inhibition processes (Vogt et al, 2018). It has been suggested that excessive motoric activity, such as fidgeting during a cognitive performance, reflects efforts to modulate attention and alertness (Hartanto et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Cases with impairment in response inhibition manifest themselves by increased commission errors with normal reaction time and reaction time variation and reflect impulsivity during the QbTest. 5 The behavior is characterized by an inability to suppress irrelevant behaviors and acting before thinking. Deficits in inhibitory control functions are also supported by extensive research evidence in relation to a clinical presentation of ADHD-combined type, 11,12 with an estimated 35 to 50% of cases of ADHD-combined type having response inhibition deficits.…”
Section: What Is the Qbtest?mentioning
confidence: 99%
“…4 The aforementioned differences in activity during the test between the neuropsychological domains of arousal/alerting functions and response inhibition are displayed in quantitative rather than qualitative distinctions. 5 It is hypothesized that increased motor activity in the arousal/alerting domain reflects an attempt to increase cortical arousal, 18 and that excessive motoric activity such as fidgeting during cognitive performance reflects efforts to modulate attention and alertness. 19 However, the difficulties in response inhibition appear to respond to mitigating environmental factors from the laboratory conditions (low perceptual load with few distractions), thus suggesting that certain types of ADHD, normally regarded as prevalent independent of changing environmental or cognitive demands, 20 may in fact be more susceptible to mitigating environmental factors than previously thought.…”
Section: Activitymentioning
confidence: 99%
See 2 more Smart Citations